A framework for the integrated analysis of metabolic and regulatory networks - Mendes, Rui (2008)
The analysis of cellular behavior and functionality is the most challenging aim of systems biology. The extensive analysis of the interactions between different classes of intra-cellular molecules reacting to genetic/environment changes can elucidate the mechanisms of regulation involved on different cellular processes. We propose a novel framework that enables the integrated analysis of metabolic and regulatory networks. The framework takes advantage on publicly available data repositories, sustaining the inference of knowledge from the integrated network. Since it is based on logic programming, it provides users with a powerful language to query information using both first and second order predicates. Also, it supports network topology analysis, motif finding and robustness evaluation. In this work, as an illustrative case study, our framework is used to build a model of the bacterium Escherichia coli K12.